The differences in business strategies employed by baratillos and boutiques - Bartolome, Hazel; Cabarrubias, Joan; Cobbol, Karen Donna Fleur; Lipardo, Karen; Servigon, Charleane
After much deliberation, the proponents of this study decided to find out the strategies employed by the various baratillo stalls and boutiques located in two malls in Iloilo City. It is the desire of the group to determine the differences between the policies of these two types of retailers, given that both engage in the apparel business and are located in the same malls. With the use of survey questionnaires, the group was able to gather relevant data about the strategies and practices of the business establishments. Additional information was derived through observation and casual interviews with salespersons. Based on the gathered data and careful analysis, it can be inferred that the major difference in the strategies of baratillo and boutiques lie in the pricing method business. Other strategies were similar, if not slightly varied.